RETRACTED: ASSESSMENT OF DESIGNED AND OPERATING TECHNICAL PROTECTION OF INFORMATION USING A MATHEMATICAL MODEL OF THE REAL PHYSICAL PROCESS OF HACKING PROTECTION - Zhurilenko, Boris (Ukrainian Information Security Research Journal, 2022)
RETRACTION NOTICE This article has been retracted by the Editorial Board in accordance with the Journal Retraction Policy. Reason for retraction: the publication does not comply with the current requirements of the legislation of Ukraine regarding the language of scientific publications. The retraction is not related to plagiarism, research misconduct, fabrication, falsification of results or other violations of academic integrity. Editorial Board of the Ukrainian Information Security Research Journal This paper shows the possibility of assessing the designed and operating technical information security (TIS) using a mathematical model of the real physical process of breaking the protection according to the experimentally obtained attempts and the time of these attempts to break. Evaluation of multi-level operating technical information protection is carried out through an equivalent single-level protection, which can be compared with the equivalent projected multi-level protection and determine its effectiveness. To obtain all the parameters of an effective single-level mathematical model of the real process of breaking TIS, at least three real attempts and their time of breaking the protection are required. Usually protection after hacking is not used, but the hacking parameters become known. If we obtain the data of three attempts to hack TIS with the same parameters of the used information protection, then it is possible to calculate all the necessary parameters of the equivalent one-level protection determined by the mathematical model of the real physical process of hacking. Since, in the open press, there are no experimental results of the study of the process of cracking technical protection, the following model was used to determine the parameters of the investigated TIS. We calculated the probability of hacking with known initial hacking parameters and built a one-level protection, from which we determined three attempts and their time of hacking, the direction of the hacking process, the intensity of hacking attempts and other data that can be determined from the real hacking process. With the help of these data, the inverse problem was solved and all unknown parameters of the investigated TIS were obtained, with a sufficiently high accuracy, coinciding with the initial data laid down in the model when designing the protection.